The Morphological Analysis of Compound Words in Kendrick Lamar's Song Lyrics on The Gnx Album - Ni Putu Lila Angelina Asmara; Yana Qomariana; Putu Lirishati Soethama (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This research is carried out to study the types and meanings of compound words found in Kendrick Lamar’s song lyrics on the GNX album. The main goal is to identify how the compound words are formed and to understand their meanings. This study uses a qualitative descriptive method. The theory from McCarthy (2002) is used to group the compound words into three types: noun compounds, verb compounds, and adjective compounds. To analyze the meanings, the study uses Booij’s (2007) theory, which explains two kinds of meaning in compounds: endocentric and exocentric. The data for this research are taken from all twelve songs on the album. The results show that the lyrics include all three types of compound words. The meanings found in the compounds include both endocentric and exocentric types. These findings are explained using simple written descriptions to give a clear understanding of the compounds found in the lyrics. The analysis shows that the lyrics contain many uncommon compound words, which shows the use of creative and modern language.